CHEMICAL AND BIOLOGICAL CONTROL OF Monilinia fructicola (WINT) HONEY AND FRUIT LACTENT INFECTION MONITORING - MOREIRA, Luciene Martins (Scientia Agraria, 2000)
The brown rot caused by Monilinia fructicola (Wint) Honey is responsible for appreciable economic damages in peach tree. The occurrence of the disease in the field, in a severe way, is conditioned to the adopted control methodology, toghether with the sources of inoculum in the orchard. The main objectives of this work were to evaluate the efficiency of the chemical and biological control of the pathogen in the field and in post-harvest, and to monitor the occurrence of Iatent infections. The experiments were accomplished in the period of May to December of 1997 and August to December of 1998, in the Phytopathology Laboratory of the Setor de Ciências Agrárias of the UFPR, in Curitiba and in the farm Seiva in the municipal district of Lapa. ln the experiment of chemical control in vitro active ingredients tested were iprodione, benomyl, captan, mancozeb, tiofanato metílico, thiram, vinclozolin, triforine, myclobutanil, procimidone, iminoctadine tris albesilate, imibenconazole, carbendazin, being selected for field control the iminoctadine, myclobutanil and iprodione. The selected fungicides plus the fosfitos of CaB and K were applied in five spraying in pre-harvest. The experimental design was in randomized complet blocks with six treatments, four replications and experimental units of nine plants. The efficiency of the applied products in the field was monitored by the incidence of the pathogen in picked fruits of the central plant of each experimental unit, in a total of 50 fruits for each pIot. These were placed in cold camera (5ºC) for six days, being proceeded the evaluations when removing them of this camera and at the three to five days of storage in the ambient. The best control was attained with flue fungicide iminoctadine tris albesillate. The antagonistic microrganisms used was isolated from peaches and plums fruits and branches harvested from the orchards of the Lapa District. Tests in vitro facilitated the selection of the best antagonistic for the accomplishment of tests in vivo in post-harvest procedures. This experiment consisted of 20 treatments using fungicides, fosfitos of CaB and K and biological agents, with three replications. The fungicidal iminoctadine and azoxystrobin and the isolated F1 and F2 (Trichothecium spp) were efficient in the control of the brown rot. The occurrence of latent infections was observed in fruits of different peaches cultivars, as in the experimental area as out of it, and also in plums and nectarines of the commercial orchard. The methodology consisted of the separation of fruits in two lots and immersion of one of them in solution of alcohol 70%, hypochlorite 2%, paraquat 2%, and the other in alcohol 70% and hypochlorite 2%, staying for two minutes in each solution. Soon alter they were put in humid camera and evaluated by the incidence of the disease.